Optimisme Investor dan Kinerja Jangka Panjang Saham Pasca Initial Public Offerings yang Listing Di Bursa Efek Indonesia: Investor Optimism and Long-Term Stock Performance After Initial Public Offerings that are Listed on the Indonesia - Mu’minatus Sholichah (Journal of Accounting Science, 2020)
This study discusses and analyzes from the perspective of investor optimism and long-term performance after the IPO in the Indonesian capital market. Observations will be made regarding the influence of investors on the increase in the length of shares after the IPO with control variables of company size, company age, offer size, the achievement of underwriters, profitability on the Indonesia Stock Exchange. This study uses data from 2004-2017, with 194 IPO companies from 2004-2015 in the Indonesian capital market. Testing is done by using two drunken linear regression. The results of this study indicate that investors in the Indonesian capital market not only consider irrational factors but also consider rational factors about the company's character in making decisions to buy IPO shares. The characteristics of the company include the size of the company and the size of the stock offering. This study provides benefits for IPO stock investors who rely on the benefits of initial stock investment in a relatively long period of time so as not to suffer losses